2017
DOI: 10.18203/2394-6040.ijcmph20170947
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and behaviour patterns regarding road safety measures among undergraduate students

Abstract: INTRODUCTIONIn most regions of the world the global epidemic of traffic injuries is still increasing.1 In India motor vehicle population is growing at a faster rate than the economic and population growth.2 It has been estimated that unless immediate action is taken, road deaths will rise to the fifth leading cause of deaths by 2030. It may result in an estimated 2.4 million fatalities per year. Half of all road traffic deaths are among pedestrians, cyclists and motorcyclists, and adults aged between 15 and 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
3
3
1
Order By: Relevance
“…7 The same distribution of participants observed by Ron et al and Ratna et al in the present study regarding behavioral patterns, 12% were involved in drunken driving. 8,9 These findings were similar to the observation in the study conducted by Swamy et al in Chandigarh. 10 In the present study, about 90 percent were aware that wearing a helmet can save a life, about the same observed by Ramya et al, observed where 98 percent of the study participants were aware of the use of a helmet.…”
Section: Discussionsupporting
confidence: 90%
“…7 The same distribution of participants observed by Ron et al and Ratna et al in the present study regarding behavioral patterns, 12% were involved in drunken driving. 8,9 These findings were similar to the observation in the study conducted by Swamy et al in Chandigarh. 10 In the present study, about 90 percent were aware that wearing a helmet can save a life, about the same observed by Ramya et al, observed where 98 percent of the study participants were aware of the use of a helmet.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that 59.6% of the respondents had adequate level of awareness regarding traffic rules and safety measures. The study finding is supported by similar study (Ratna et al, 2017) which revealed that the awareness regarding road safety measures among the study participants was satisfactory but interpretation of traffic signs was poor (30.5%). The findings variation might be due to variation in setting, socio demographic characteristics of the respondents.…”
Section: Discussionsupporting
confidence: 79%
“…Simple measures such as awareness and practice of road safety measures can effectively reduce the impact of RTAs on the people's lives. Awareness generation and orientation towards road safety issues among the students should be done through periodic trainings (Ratna et al, 2017). Nepalese roads are one of the most dangerous in the world and chances of vehicle crashes are more than 100 times higher than in Japan and 10 times higher than in India.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, more no of female participants, 30 (45.54%) wore a helmet while riding a two-wheeler compared to males 20 (30.37%). Ratna et al in their study observed that overall, 74% wore a helmet (Ratna et al, 2017). The number of participants wearing a helmet in our study was far less, and this can be attributed to the relaxed law on helmet usage in our city and state.…”
Section: Resultscontrasting
confidence: 47%